Effect of Astragali radix extract on pharmacokinetic behavior of dapagliflozin in healthy and type 2 diabetic rats - Du, Wandi; Hu, Jiarong; Liang, Jingru; Yang, Xiaolei; Fang, Boyu; Ma, Guo (Frontiers in Pharmacology, 2023)
Objective: This study aimed to investigate effect of antidiabetic herb Astragali Radix (AR) on pharmacokinetic behavior of dapagliflozin (DAPA) in healthy rats and type 2 diabetes mellitus (T2DM) rats. Methods: The T2DM rats were induced by high-fat diet (HFD) and intraperitoneal injection of streptozotocin (STZ). Concentrations of DAPA in healthy and T2DM rat plasma were determined by UPLC-MS/MS method. Effect of AR extract (ARE) on pharmacokinetic behavior of DAPA in healthy and T2DM rats was evaluated, respectively. Results: The diabetes status and co-administrated with ARE significantly affected pharmacokinetic behaviors of DAPA in the rats. Compared to that in healthy rats, tmax of DAPA significantly shortened, its Cmax significantly increased in T2DM rats, and its t1/2, V, AUC, CL and MRT kept unchanged. When ARE was co-administrated with DAPA, Cmax of DAPA significantly increased, its tmax and MRT significantly decreased, and its t1/2, V, AUC and CL kept unchanged in healthy rats. tmax and Cmax of DAPA significantly decreased, its t1/2 and V significantly increased, and its AUC, CL and MRT were unchanged in T2DM rats when ARE was co-administrated with DAPA. Co-administration of DAPA and ARE promoted absorptive rate of DAPA, increased its extravascular tissue distribution, and prolonged its duration of action. ARE did not cause accumulation of DAPA in vivo. Conclusion: Both disease status of T2DM and co-administration of ARE affect pharmacokinetic behavior of DAPA in vivo. Potential pharmacokinetic interactions may occur in vivo when herbs and drugs are co-administrated, which may affect efficacy and safety of drugs.